Using Interactive Canva Media to Improve Elementary School Students' Description Writing Skills - Fattalia Zikra; Zainal Abidin; Novi Diana (Institut Agama Islam (IAI) Faqih Asy'ari Kediri, 2026)
Writing instruction in Indonesian elementary education is directed at developing students' language competence, one component of which is descriptive-text writing. Preliminary observation at SD Negeri 6 Muara Dua, North Aceh Regency, indicated that fourth-grade students' descriptive writing achievement remained below the school's Learning Achievement Criteria (Kriteria Ketercapaian Tujuan Pembelajaran/KKTP), with the class mean score at 68.4 and only 37.0% of the 27 students reaching the minimum score of 74. This condition was attributable to limited use of engaging instructional media and predominantly teacher-centred practices. This study aimed to improve the learning outcomes and learning activity of fourth-grade students in descriptive-text writing through interactive Canva-based media. Using a two-cycle Classroom Action Research (CAR) design following the Kemmis and McTaggart spiral model (planning, action, observation, reflection), data were collected through writing tests, structured activity-observation sheets, and documentation, and were analysed using quantitative descriptive statistics (mean scores and mastery-learning percentages) complemented by qualitative analysis (data reduction, data display, and conclusion drawing). The findings show that the class mean score increased from 68.4 (pre-action) to 76.8 (Cycle I) and 85.6 (Cycle II), while the percentage of students achieving the KKTP rose from 37.0% to 70.4% and 88.9%, exceeding the pre-set 75% success indicator. Student learning activity likewise increased across the two cycles, as reflected in observation scores for attention, participation, and confidence in presenting written work. These findings indicate that interactive Canva-based media constitutes an effective pedagogical strategy for strengthening both the process and the product of descriptive writing in elementary classrooms.